Application of Positive and Negative Board Based on Montessori Method on Junior High School Students' Mathematical Connection Abilities - Susiaty, Utin Desy; Firdaus, Muhamad (Department of Mathematics Education Program IPI Garut, 2024)
Tujuan dari penelitian ini adalah untuk mengetahui seberapa baik aplikasi papan positif negatif berbasis metode Montessori terhadap kemampuan koneksi matematis siswa SMP. Subjek penelitian adalah siswa di kelas VII SMP. Data dikumpulkan menggunakan teknik pengukuran dan teknik komunikasi tidak langsung. Soal tes kemampuan adalah alat pengumpul data. Berdasarkan hasil pengembangan, penelitian, dan diskusi tentang penggunaan papan positif negatif berbasis metode Montessori terhadap kemampuan koneksi matematis siswa SMP, dapat disimpulkan bahwa pengembangannya mencapai tingkat kelayakan yang sesuai dengan kriteria validitas, praktisitas, dan efektifitas. The aim of this research is to find out how well the positive and negative board application based on the Montessori method affects junior high school students' mathematical connection abilities. The research subjects were students in class VII of junior high school. Data was collected using measurement techniques and indirect communication techniques. Ability test questions are a data collection tool. Based on the results of development, research and discussions regarding the use of positive and negative boards based on the Montessori method on junior high school students' mathematical connection abilities, it can be concluded that the development has reached a level of feasibility that is in accordance with the criteria of validity, practicality and effectiveness.